Motivational Interviewing in Childhood Obesity Treatment - Borrello, Maria; Pietrabissa, Giada; Ceccarini, Martina; Manzoni, Gian M.; Castelnuovo, Gianluca (Frontiers in Psychology, 2015)
Obesity is one of today’s most diffused and severe public health problems worldwide. It affects both adults and children with critical physical, social and psychological consequences. The aim of this review is to appraise the studies that investigated the effects of motivational interviewing techniques in treating overweight and obese children. The electronic databases PubMed and PsychINFO were searched for articles meeting inclusion criteria. The review included studies based on the application of MI components and having the objective of changing BMI in overweight or obese children from age 2 to age 11. Six articles have been selected and included in this review. Three studies reported that MI had a statistically significant positive effect on BMI and on secondary obesity-related behaviour outcomes. MI can be applicable in the treatment of overweight and obese children, but its efficacy cannot be proved given the lack of studies carried out on this specific sample.